Abundance, diversity and daily activity of terrestrial mammal and bird species in disturbed and undisturbed limestone habitats using camera trapping, Central Thailand - MANANYA PLA-ARD; WIPAVEE HOONHEANG; BUNYATHIPORN KAEWDEE; TARAPON PANGANTA; KHWANRUTAI CHARASPET; NORASET KHOIESRI; PAANWARIS PAANSRI; PEMIKA KANKA; YUWARAK CHANACHAI; JIDAPHA THONGBANTHUM; PHANITSUPHA BANGTHONG; ronglarp sukmasuang (Society for Indonesian Biodiversity, 2021)
Abstract: Pla-ard M, Hoonheang W, Kaewdee B, Panganta T, Charaspet K, Khoiesri N, Paansri P, Kanka P, Chanachai Y, Thongbanthum J, Bangthong P, Sukmasuang R. 2021. Abundance, diversity and daily activity of terrestrial mammal and bird species in disturbed and undisturbed limestone habitats using camera trapping, Central Thailand. Biodiversitas 22: 3620-3631. This study on the abundance, diversity and daily activity of terrestrial mammal and bird species was conducted in the limestone mountainous area of Central Thailand, located on the east of Dong Phaya Yen-Khao Yai forest complex. Camera traps were placed in both habitats disturbed by limestone mining and undisturbed habitat areas. From the study, a total of 38 species of mammals and birds from 27 families in 13 orders were recorded, including 15 species of mammals from 6 orders, 12 families and 23 species of birds from 14 families in 7 orders. Fifteen species of mammals were recorded in the undisturbed area and 11 were recorded in the disturbed area, with the Malayan Pangolin, Small Indian Civet and Grey-bellied Squirrel found in the undisturbed area. However, the number of bird species in the limestone mining area was larger than in the undisturbed area. It was also found that there was no difference in the overall abundance and diversity of mammalian species between disturbed and undisturbed areas, which is not in accordance with the hypothesis. But in the case of wild birds, the relative abundance of wild birds was found to differ significantly between areas. A high number was found in the areas with mining activities, although there was no difference in the diversity index of the two areas. However, it was found that when the combined data was analyzed, there was a significant difference in the daily activity of both mammals and wild birds in both areas. Many rare wildlife species were recorded during this study, for example, the Malayan Pangolin, Serow, Northern Pig-tailed Macaque, Rufous Limestone-babbler, Golden Jackal, Leopard Cat, Large-toothed Ferret Badger, Small Asian Mongoose, Common Palm Civet, Small Indian Civet, Malayan Porcupine. The key measure proposed is to preserve some natural habitats within the areas with mining activities, as wildlife remains in the area.